2017
DOI: 10.4172/2165-7025.1000325
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Capacitive and Resistive Electric Transfer on Tissue Temperature, Muscle Flexibility, and Blood Circulation

Abstract: Introduction: The differences between Capacitive and Resistive electric transfer (CRet) and hot pack (HP) in their effects on tissue temperature, muscle flexibility, and blood circulation are unknown. This study aimed to clarify the effect of CRet and HP on tissue temperature, muscle flexibility, and blood circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…The main underlying mechanism is considered to be the rise in temperature associated with electromagnetic energy, which triggers oscillation and friction forces of charged molecules, such as proteins and ions. This increase in temperature has been described at a superficial level (10-15 mm, which is believed to reflect the state of the subcutaneous adipose tissue and fascia), but also at a deeper level (20-30 mm, which is supposed to reflect the state of the muscle layer) [7,8,13]. The mild elevation of the temperature achieved in these studies was enough to accelerate metabolic activity and to improve local circulation.…”
Section: Changes In Energetic Parametersmentioning
confidence: 55%
See 2 more Smart Citations
“…The main underlying mechanism is considered to be the rise in temperature associated with electromagnetic energy, which triggers oscillation and friction forces of charged molecules, such as proteins and ions. This increase in temperature has been described at a superficial level (10-15 mm, which is believed to reflect the state of the subcutaneous adipose tissue and fascia), but also at a deeper level (20-30 mm, which is supposed to reflect the state of the muscle layer) [7,8,13]. The mild elevation of the temperature achieved in these studies was enough to accelerate metabolic activity and to improve local circulation.…”
Section: Changes In Energetic Parametersmentioning
confidence: 55%
“…In addition, a summing effect appeared to happen in the second session of CRET in these parameters, since SL was longer on the second day (26, 30 and 36 h after the first session) compared to the first day (2, 6 and 12 h). The duration of the increased temperature and other physiological effects caused by CRET have not been defined exactly, and skin, superficial and deep temperature, blood flow and hemoglobin saturation, have been measured up to only to 30 min post-application [7,8,13]. Moreover, several in vitro studies have shown that CRET application also exerts non-thermal effects, consisting of a modulation of cellular activity and changes in membrane transport [18,19].…”
Section: Changes In Stride Spatiotemporal Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiofrequency treatment is a therapeutic approach used in the treatment of most musculoskeletal and sports injuries. One of the most effective radiofrequency treatments is Indiba ® Activ treatment at 448 kHz, a frequency that has been associated with pain reduction and improved functionality in patients with musculoskeletal disorders [2][3][4] . This wavelength promotes ion mobilisation between the intracellular and extracellular matrix and restores cell membrane permeability.…”
Section: Introductionmentioning
confidence: 99%
“…This device delivers radiofrequency energy, which passes between an active and inactive electrode, and generates heat within the body 30 , 31 ) . Previous studies indicated that CRet was more effective in improving blood circulation than a hot pack, which is a conventional thermotherapy modality used frequently in clinical practice 32 , 33 ) . Improving blood circulation would play an important role in the enhancement of muscle recovery after fatigue 34 , 35 ) .…”
Section: Introductionmentioning
confidence: 99%